QUALITY OF TILAPIA NUGGETS FORTIFIED WITH MORINGA LEAF FLOUR - Dwi Sagita; Baiq Rien Handayani; Siska Cicilia (Jurnal Perikanan Unram, 2024)
Nugget is a restructured meat from ground and molded meat. Generally nuggets are made from  chicken. To enrich the nutritional content, the ingredients for making nuggets were diversified using tilapia fish meat and moringa leaf flour. This research aims to determine the effect of fortification of Moringa leaf flour on the quality of tilapia fish nuggets. This research used a Completely Randomized Design (CRD). The treatment consisted of fortification of Moringa leaf flour (TK), namely TK1 (0%), TK2 (5%), TK3 (10%), TK4 (15%), TK5 (20%) and TK6 (25%). Analysis of the observation data was carried out using Anova and BNJ further tests. The nugget quality parameters in this study were chemical and organoleptic parameters. Moringa leaf flour fortification had a significant difference on all nugget quality parameters except color. Moringa leaf flour could improve the quality of tilapia fish nuggets by increasing the protein content by 0.5-13.18% and producing tilapia fish nuggets which have a vitamin A (ß-carotene) content of 1.82-20.76 %. Fortification of foringa leaf flour with a concentration of 10% was the best treatment to produce tilapia fish.